If it's not what You are looking for type in the equation solver your own equation and let us solve it.
49=u+6u
We move all terms to the left:
49-(u+6u)=0
We add all the numbers together, and all the variables
-(+7u)+49=0
We get rid of parentheses
-7u+49=0
We move all terms containing u to the left, all other terms to the right
-7u=-49
u=-49/-7
u=+7
| 9x+5=-25 | | 2^-2k=16 | | 3x-55=23 | | 7x1+18=74 | | 4v+2=-28.4 | | 9+2n=27 | | 3x+47+10-27+x=x | | 7=2n=-3 | | -6(1)-4y=-6 | | 113=999+n | | 0=2(x-7)/7-7(x-2)/2 | | X^2+140x+12800=0 | | 2x+30+2x+54=90 | | 3 = d3− 1 | | 55-n=51 | | 2x+302x+54=90 | | 6z-18=3z | | -4x-6(-9)=16 | | 2x+44=96 | | x^2-8x+16/x^2-16=10/30 | | 180=7x3(-6x+15) | | 27+x-3x+47=10 | | 3/4m+10=40 | | -1/9(z+3)=2/3(z-2/3) | | 18=2j+2 | | 3x-5(x-2)=-8+2x+6 | | y=-3/5(-5)+1 | | -6x-3(-1)=9 | | |6-x/6|=11 | | 4x+38=8x-6 | | 4(10x+25)=420 | | 21+2.5w=6+5.7w-3, |